Animal Endo-SiRNAs Methods and Protocols - Werner, Andreas; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
Animal Endo-SiRNAs: Methods and Protocols presents a variety of approaches to investigate endo-siRNAs.  These include protocols applicable to study short RNAs expressed at a low level and model systems that are particularly suitable to investigate specific aspects of endo-siRNAs, their synthesis, their genomics or regulatory role. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.  Authoritative and practical, Animal Endo-SiRNAs: Methods and Protocols contains practical tips that are absent in standard lab manuals.  .
Targeted Small Non-coding RNA Directed Gene Activation in Human Cells -- Isolation of Chromatoid Dodies from Mouse Testis as a Rich Source of Short RNAs -- Generation of Endo-siRNAs in Xenopus laevis Oocytes -- Analysis of Endo-siRNAs in Drosophila -- Methods for Studying the Biological Consequences of Endo-siRNA Deficiency in Drosophila melanogaster -- Small RNA Library Cloning Procedure for Deep Sequencing of Specific Endogenous siRNA Classes in Caenorhabditis elegans -- Assays for Direct and Indirect Effects of C. elegans Endo-siRNAs -- Extraction and Non-radioactive Detection of Small RNA Molecules -- p19 Mediated Enrichment and Detection of siRNAs -- Detection of Small non-coding RNAs by in situ Hybridization using Probes of 2’-O-Methyl RNA + LNA -- Enhanced Detection of Small RNAs using a non-Radioactive Approach -- Computing siRNA and piRNA Overlap Signatures -- Isolation of Small Interfering RNAs using Viral Suppressors of RNA Interference -- Computational Analysis, Biochemical Purification and Detection of tRNA-derived Small RNA Fragments -- Differential DNA Methylation Patterns in Endo-siRNAs Mediated Silencing of LINE-1 Retrotransposons.
Keywords: Human genetics; Human Genetics